Effect of blockchain technology adoption on supply chain adaptability, agility, alignment and performance. Issue 12 (1st August 2019) - Sheel, Ashutosh; Nath, Vishnu
Abstract : Purpose: The purpose of this paper is to illustrate how blockchain technology can improve supply chain adaptability, alignment and agility which collectively enhance competitive advantage which in turn influences firm performance. Design/methodology/approach: The conceptual framework of the present study is developed by conducting an extensive literature review on blockchain technology, supply chain adaptability, alignment, agility and competitive advantage. The sample data were collected from 397 supply chain practitioners in India to validate the conceptual model. Confirmatory factor analysis was conducted to ascertain the validity of the measures used and a structural model was analyzed for testing the proposed conceptual framework. Findings: The results of the present study show that blockchain technology can improve supply chain adaptability, alignment, agility which lead to competitive advantage, which leads to better firm performance. Besides, trust generated through blockchain use also increases firm performance. Research limitations/implications: Currently, the respondents do not have practical experience of using blockchain technology. They have responded based on their knowledge about supply chain and blockchain which they acquired from published sources. Different supply chains require different strategic choices and different information needs. But the present study assumes that all supply chain needs are identical. The present study assumes that government regulations regarding blockchain technology are favorable; however, currently, there is no legal framework to address blockchain technology. The findings of the current study indicate that companies not only should create more awareness regarding blockchain but also should actively work with IT companies that are engaged in developing blockchain-based supply chain solution. Managers, as well as IT companies and academicians, should join hands to study and develop a framework for regulating blockchain technology and suggest these to the policy actors. Practical implications: The present study shows that supply chain practitioners are confident that blockchain technology will help improve supply chain parameters. These findings can help IT companies and their marketers for developing and promoting blockchain-based IT applications. In addition, the important implication for supply chain practitioners is that blockchain helps in creating a competitive advantage and increases firm performance. Originality/value: The effect of IT on important supply chain variables has been studied in the past; however, there is not a single study which sheds light on how disruptive technologies such as blockchain will affect supply chain adaptability, alignment, agility and firm performance.